1998
DOI: 10.1021/ja973956r
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Oxidation in the Troposphere. Theoretical Investigation on the Possible Competition of Three Postulated Reaction Channels

Abstract: Three different attacks of 3 Σ g O 2 on the hydroxycyclohexadienyl radical intermediate I (generated from the reaction of OH • with benzene) have been studied by Density Functional Theory. Both abstraction by O 2 of the hydrogen gem to OH in I (affording phenol) and O 2 addition to the π-delocalized system of I (producing a hydroxycyclohexadienyl peroxyl radical intermediate) appear to be very viable, with ∆H q ) 3-4 kcal mol -1 . The former reaction is exothermic by 27 kcal mol -1 , the latter only by 1 kcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 16 publications
6
70
0
1
Order By: Relevance
“…The reversibility, also indicated in Figure 1, was predicted theoretically 9,17,18 and was known from liquid phase, 19 but the peroxy radical was found to be unexpectedly short-lived (2.5 ms in synthetic air) on account of competing loss processes of the adduct:…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The reversibility, also indicated in Figure 1, was predicted theoretically 9,17,18 and was known from liquid phase, 19 but the peroxy radical was found to be unexpectedly short-lived (2.5 ms in synthetic air) on account of competing loss processes of the adduct:…”
Section: Introductionsupporting
confidence: 54%
“…18,37 Recently Molina et al 38 investigated the intermediates of the OH + toluene reaction in the presence of O 2 by chemical ionization mass spectrometry. A mass peak at m/e ) 141 was attributed to the peroxy radical (III) while cyclization forming the bridged species (IV) was assumed to be unimportant due to the short residence time.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several authors studied the transient absorption of HCHD in the presence of O 2 , Johnson et al (2002), Raoult et al (2004), Grebenkin and Krasnoperov (2004)). provided first evidence of a fast equilibrium (7/-7) in the gas phase, predicted theoretically by Lay et al (1996) and Ghigo and Tonachini (1998) but already observed in water by Pan and Von Sonntag (1990).…”
Section: The Adduct Reaction With Omentioning
confidence: 54%
“…It is noted that these products may alternatively be generated from the initial OH adduct by a direct reaction with O 2 (e.g. Lay et al, 1996;Ghigo and Tonachini, 1998). However, the overall chemistry of these representations is indistinguishable, such that the representation employed is consistent with either mechanism.…”
Section: Ro 2 Radicals From H-abstractionmentioning
confidence: 99%